Motivation in doing amateur Muay Thai of Thai boxers participating in the 41st National Games, Chiang Mai - Petchkeaw, Supharp (Academic Journal of Thailand National Sports University, 2022)
This research aimed to investigate motivation in doing amateur Muay Thai of Thai boxers in the 41st National Games, Chiang Mai. The subjects were 227 amateur Thai boxers; 149 male boxers and 78 female boxers. A questionnaire was used to collect data. Descriptive statistics (percentage,arithmetic mean, and standard deviation) were utilized for data analysis. Obtained data was presented in the form of tables with desctription. The findings of this research revealed that the amateur Thai boxers expressed their motivation at a high level for all six related areas as follows respectively.Health area, the total mean was 4.42. When considering each item, the item in that Muay Thai enhances healthy body was indicated at a highest level.Future progress area, the total mean was 4.35. When looking at each item, the item concerning their need for supporters was at a highest level.Love, aptitude, and interests area, the total mean was 4.33. When individual items were considered, the item in that Muay Thai skills support ability of self defense was specified at a highest level. Reputation area, the total mean was 4.31. When looking at each item, the item related to their wish of being famous sportsmen and bringing the reputation to the country was at a highest level.Concerned people area, the total mean was 4.12. When considering each item, the item in that their family are proud of and support them to be amateur Thai boxers was indicated at a highest level. For incomes and benefits area, the total mean was 4.10. When individual items were considered, the item concerning their need to attend in a university by an athlete quota system was rated at a highest level.